Endothelial Dysfunction and Diabetes: Effects on Angiogenesis, Vascular Remodeling, and Wound Healing - Gopi Krishna Kolluru; Shyamal C. Bir; Christopher G. Kevil (International Journal of Vascular Medicine)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by inappropriate hyperglycemia due to lack of or resistance to insulin. Patients with DM are frequently afflicted with ischemic vascular disease or wound healing defect. It is well known that type 2 DM causes amplification of the atherosclerotic process, endothelial cell dysfunction, glycosylation of extracellular matrix proteins, and vascular denervation. These complications ultimately lead to impairment of neovascularization and diabetic wound healing. Therapeutic angiogenesis remains an attractive treatment modality for chronic ischemic disorders including PAD and/or diabetic wound healing. Many experimental studies have identified better approaches for diabetic cardiovascular complications, however, successful clinical translation has been limited possibly due to the narrow therapeutic targets of these agents or the lack of rigorous evaluation of pathology and therapeutic mechanisms in experimental models of disease. This paper discusses the current body of evidence identifying endothelial dysfunction and impaired angiogenesis during diabetes.